Determining the main factors of Islamic banks’ profitability in Indonesia: Does Covid-19 crisis play an important role? - Ahmad Munawar; Sulaeman (Faculty of Business & Economics, Universitas Islam Indonesia, 2022)
Purpose – This research aims to investigate the main factors of Islamic banks’ profitability before and after the pandemic COVID-19 in Indonesia. Methodology – The sample of this study is ten Islamic commercial banks that have complete data and are registered with Bank Indonesia. The data was analyzed by using a data panel regression estimation model based on the best estimation model which is the random effect model or REM. Findings – Based on the result of the REM model, the study finds that both Islamic banks' internal variables such as NPF and OEF except CAR and FDR, and Islamic bank’s external variables such as the Covid-19 crisis variables are significant in determining Islamic banking profitability In Indonesia. Implications – The present research has implications for Islamic bank management and policy-makers as well as researchers.Originality – This study will become one of the pioneers to examine empirically determining the main factors of Islamic banks' profitability before and post-Covid-19 in Indonesia. The findings will contribute to minimizing the negative impact of economic crises like the Covid-19 outbreak in Indonesia.